We’re all in this together: Post COVID-19 Opportunities for International Library Cooperation - Hickok, John (Access: An International Journal of Nepal Library Association, 2022)
The Covid-19 pandemic of 2020-2022 brought worldwide disruption and suffering. It also made us realize “We’re all in this together”- among all humanity, internationally— as the virus so easily crossed borders worldwide. Amid this global tragedy, examples of international cooperation also arose: distribution of vaccines, coordination of travel safety protocols, cooperation in humanitarian aid, etc. In this same spirit of international cooperation, libraries can consider opportunities for international library cooperation. These include international library associations and conferences, sister-library programs, collaborative partnering, and cross-cultural outreach efforts. This article will highlight these opportunities, noting how such cooperation brings us closer—not only as library professionals, but among all humanity.